Introducing a Mobile Payment System to an Emerging Economy's Mobile Phone Subscriber Market. An Actor Network Perspective. Issue 1 (5th December 2017) - Harry, Ricardo; Sewchurran, Kosheek; Brown, Irwin
Abstract: The introduction of mobile payment systems to the African continent has given rise to a significant number of published research material. These research projects have addressed issues such as needs assessment, design of systems, areas of application, adoption, adaptation and impact assessment. Few studies have engaged with a deeper understanding of the interactions and relationships that are created amongst stakeholders of a national mobile payment system. A mobile payment system, similar to the one introduced in Kenya in 2007, was introduced to the South African economy in 2010. The South African economy is renowned for its dual economic system that consists of both developing and developed components. This paper focuses on understanding the processes involved in introducing the mobile payment system and the reaction of the South African mobile subscriber market to its introduction. Actor Network Theory was used as the theoretical lens, which gave rise to an understanding of the networks of relations formed amongst the actors affected by the mobile payment system introduction.